The Concepts and Determinants of Manufacturing Flexibility - Mohd Ghazali, Maarof; Gusman, Nawanir; Muhammad, Fakhrul
Manufacturing companies nowadays are facing intense global challenges to sustain in this competitive market. As the global market are becoming more globalized and many new technologies being introduce, it has changed the demand preference for new products. The new market demand requires that the manufacturing firms to deliver customize products that can meet the individual customer’s needs. This has created high level of market uncertainty and add complexity to the manufacturing processes set-up in many manufacturing companies. Manufacturing flexibilities provide a better way for manufacturers to overcome this uncertainty. This article will examine the contributing factors that can assist manufacturing firms to implement effective manufacturing flexibility in their manufacturing processes. Method used in conducting this review analysis is based on analysing the literature review done by the past researchers. This study reveals that the contributing factors can be simplified into three categories, namely advance manufacturing technology (AMT), organizational and environment. Findings from this study is expected to expand the knowledge on manufacturing flexibility requirements. In addition, this study can help industrial practitioners to implement manufacturing flexibility in a much better way.